2021
DOI: 10.3389/fonc.2021.753791
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lung Cancer by ATR-FTIR Spectroscopy and Chemometrics

Abstract: Lung cancer is the leading cause of cancer-related death in the world. Early diagnosis has great significance for the survival of patients with lung cancer. In this paper, attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy combined with chemometrics was used to study the serum samples from patients with lung cancer and healthy people. The results of spectral band area comparison showed that the concentrations of protein, lipid and nucleic acids molecules in serum of patients with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…The peak at assigned to the amide group is also higher in PCa patients, which implies an increase of protein concentration, and is consistent with the literature that found higher amide peak in breast cancer, 48 lung cancer, 49 and colorectal cancer tissues. 50 One of the proposed explanations for this difference is that it appears to inform on biological changes of malignancy such as increased alterations in protein structures and protein unfolding.…”
Section: Discussionsupporting
confidence: 91%
“…The peak at assigned to the amide group is also higher in PCa patients, which implies an increase of protein concentration, and is consistent with the literature that found higher amide peak in breast cancer, 48 lung cancer, 49 and colorectal cancer tissues. 50 One of the proposed explanations for this difference is that it appears to inform on biological changes of malignancy such as increased alterations in protein structures and protein unfolding.…”
Section: Discussionsupporting
confidence: 91%
“…FTIR spectra of serum were measured in the range of 4000–600 cm −1 by a Frontier spectrometer (Perkin Elmer) with the same test method as in our previous work ( Yang et al, 2021a ). Each IR spectrum was an accumulation of 32 scans at a resolution of 4 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Vibrational spectroscopy is an important tool in the field of analytical chemistry and bioanalysis, of which Fourier transform infrared (FTIR) spectroscopy and Raman spectroscopy have been widely used in cancer diagnosis in recent years ( Auner et al, 2018 ; Christensen et al, 2019 ; Baiz et al, 2020 ). In our previous work, we studied the serum samples of patients with lung cancer and healthy people using FTIR spectroscopy and found that the concentrations of protein, lipid, and nucleic acid molecules in the serum of patients with lung cancer were higher than those of healthy people ( Yang et al, 2021a ). Song et al classified the tissues of healthy people and patients with lung squamous cell carcinoma using Raman spectroscopy combined with principal component analysis–linear discriminant analysis (PCA-LDA) ( Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The standard normal variate (SNV) normalization was employed to normalize the spectra [46]. Regions of 3000-2800 cm −1 (lipid), 1700-1500 cm −1 (protein), and 1270-960 cm −1 (nucleic acid) were selected for analysis [39,47]. The spectral band area calculation was done with SpectraGryph version 1.2.14 (Dr. Friedrich Menges, Oberstdorf, Germany).…”
Section: Spectral Band Area Analysismentioning
confidence: 99%
“…Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy has emerged as a powerful tool in the medical diagnostic field [36,37]. ATR-FTIR has been extensively explored to identify molecular vibrations of biomolecules in various biological samples that are useful for monitoring health status [38,39]. Some advantages provided by ATR-FTIR include the ease of handling samples with relatively short measurement duration (only a few minutes), a small amount of required sample volume, a reagent-free approach, and high signal to noise ratio output that facilitates chemometric analysis.…”
Section: Introductionmentioning
confidence: 99%